A strategic management framework for the commercialisation of multi-technology renewable energy systems: The case of concentrating solar power technologies in South Africa - Prentice, Kennedy Gregory Stuart (Stellenbosch : Stellenbosch University, 2018)
Thesis (MEng)--Stellenbosch University, 2018.